Enhanced recovery and dissolution of griseofulvin nanoparticles from surfactant-free nanocomposite microparticles incorporating wet-milled swellable dispersants. (November 2014) - Bhakay, Anagha; Azad, Mohammad; Vizzotti, Emanuel; Dave, Rajesh N.; Bilgili, Ecevit
Abstract Nanocomposite microparticles (NCMPs) incorporating drug nanoparticles and wet-milled swellable dispersant particles were investigated as a surfactant-free drug delivery vehicle with the goal of enhancing the nanoparticle recovery and dissolution rate of poorly water-soluble drugs. Superdisintegrants were used as inexpensive, model, swellable dispersant particles by incorporating them into NCMP structure with or without wet-stirred media milling along with the drug. Suspensions of griseofulvin (GF, model drug) along with various dispersants produced by wet-milling were coated onto Pharmatose® to prepare NCMPs in a fluidized bed process. Hydroxypropyl cellulose (HPC, polymer) alone and with sodium dodecyl sulfate (SDS, surfactant) was used as base-line stabilizer/dispersant during milling. Croscarmellose sodium (CCS, superdisintegrant) and Mannitol were used as additional dispersants to prepare surfactant-free NCMPs. Nanoparticle recovery during redispersion and dissolution of the various GF-laden NCMPs were examined. Suspensions prepared by co-milling GF/HPC/CCS or milling GF/HPC/SDS were stable after 30 h of storage. After drying, due to its extensive swelling capacity, incorporation of wet-milled CCS in the NCMPs caused effective breakage of the NCMP structure and bursting of nanoparticle clusters, ultimately leading to fast recovery of the GF nanoparticles. Optimized wet co-milling and incorporation of CCS in NCMP structure led to superior dispersant performance over incorporation of unmilled CCS or physically mixed unmilled CCS with NCMPs. The enhanced redispersion correlated well with the fast GF dissolution from the NCMPs containing either CCS particles or SDS. Overall, swellable dispersant (CCS) particles, preferably in multimodal size distribution, enable a surfactant-free formulation for fast recovery/dissolution of the GF nanoparticles.